(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
In this paper, an autocorrelation and cross-correlation analysis of the flow of the Kupa and Sava Rivers was performed. The analysis was performed at hydrological stations close to the confluence of these two rivers near the city of Sisak, based on data of mean daily flows and daily precipitation. The analysed time period is from 2008 to 2017, with the series being divided into two parts of five years each, from 2008 to 2012 and 2013 to 2017. Daily flow data were measured at the hydrological stations Farkašić on Kupa River and Crnac on Sava River, and data on precipitation at the main meteorological station and the automatic meteorological station Sisak. The maximum value of the cross-correlation function between hydrological stations at Kupa and Sava Rivers is very high, but at a time lag of zero days. The value of the cross-correlation function remains high up to 0.6 and up to 4 days lag. The cross-correlation function between precipitation and hydrological data has a very low maximum value.